Kobi'ler ve girişimcilik - Demirel, M. Mesut (Fen Bilimleri Enstitüsü, 2004)
Small and middle scale enterprise and entrepreneurship
Small and middle scale enterprise and entrepreneurship
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2004
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 2004
Keywords: Yeni iş girişimleri; Girişimcilik; Küçük işletmeler; New business enterprises; Entrepreneurship; Small business